Optimization of spacing and nutrient levels in browntop millet for enhancing yield and economic benefits - Ashoka, P; Mahantesh, B N (Plant Science Today, 2026)
Browntop millet is gaining importance in recent years as a sustainable and viable crop in semi-arid regions of India due to its climate resilience and nutritional richness. Despite its potential, the crop’s inherent productivity and wider adoption are restricted by limited spacing and nutrient application. Thus, the present study was formulated to optimize the plant spacing and nutrient levels to attain higher yield levels. A field study was conducted for three consecutive kharif seasons (2022-2024) in a split-plot design with three replications. The main plot comprised of three varied levels of row spacings (30, 45 and 60 cm), while subplot consisted of three levels of nutrient application (30:15:15,45:22.5:22.5 and 22.5:10:10 NPK (nitrogen:phosphorus:potassium) kg/ha). The results from the pooled analysis revealed that row spacing with 45 cm resulted in significantly higher grain yield (1604 kg/ha) compared to 30 cm and 60 cm row spacings. Among the varied nutrient levels, the application of higher dose of nutrients, specifically 45:22.5:22.5 kg NPK/ha, recorded significantly higher grain yield, straw yield and net returns up to 14.42, 14.36 and 23.08 % respectively, compared to lower levels of nutrient application. This higher rate also facilitated greater nutrient uptake and maintained higher soil available nutrients post-harvest of the browntop millet crop. Thus, for attaining higher yield, nutrient use efficiency and economic benefits in browntop millet, 45 cm row spacing coupled with application of 45:22.5:22.5 kg NPK/ha found to be optimum under semi-arid conditions of Northern Karnataka.